Feasibility Study on Electrical Properties of 20 kV Polymeric Insulator Dry Test and Rainwater Test - Abdul Syakur; A.I.W. Nugroho; Hermawan Hermawan (Jurnal Rekayasa Elektrika, 2021)
Insulator is a very important equipment in an electric power system. Ceramic insulators have been widely used to support conductors in 20 kV power lines. The problem of ceramic insulators is that they are heavy, easily contaminated on the surface and require a lot of energy in the manufacturing process. Therefore, polymer insulators were developed. This paper presents the design of an epoxy resin polymer insulator with Titanium Dioxide (TiO2) as a nanofiller. The leakage current test was carried out in a high voltage laboratory by applying an AC high voltage of 50 Hz to the insulator dry conditions and the insulator wetted by rainwater contaminants. The results of the leakage current test in dry conditions are 487.6 μA, rainwater contaminated conditions are 594.93 μA, insulation resistance in dry conditions is 2.07 G-Ohms, and contaminated conditions are 1.41 G-Ohms. Based on the test results show that the insulator leakage current increases up to 22% when the surface of the insulator is contaminated with rainwater. Meanwhile, the insulation resistance decreased by up to 32% in conditions contaminated with rainwater. The value of leakage current and insulation resistance indicates that the epoxy resin insulator with TiO2 as filler is electrically feasible to use.